Hubungan Faktor Structural, Proses, Outcome dan Kualitas Pelayanan Posyandu Integrasi Layanan Primer Dengan Kepuasan Masyarakat di Wilayah Kerja Puskesmas Paciran Kabupaten Lamongan - Abdul Wakhid; Ahmad Zakaria; Zulfikar As`ad (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to identify service aspects that still need improvement to support the effectiveness of primary health care transformation at the community level. This study uses a quantitative approach with a cross-sectional analytical study design. The analytical method used is path analysis to test a complex theoretical model regarding the direct and indirect relationships between variables. This study was conducted in the working area of ​​the Paciran Community Health Center. The implementation of Integrated Posyandu in the working area of ​​the Paciran Community Health Center is still in the development stage with the condition of the structure, process, and outcome at a sufficient level. The quality of service is mostly perceived in the moderate category, with the level of satisfaction dominated by the satisfied category, reflecting great potential for continued improvement.